2014
DOI: 10.1186/1471-2407-14-394
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic relevance of induced and spontaneous apoptosis of disseminated tumor cells in primary breast cancer patients

Abstract: BackgroundAn imbalance between cell proliferation and programmed cell death can result in tumor growth. Although most systemic cytotoxic agents induce apoptosis in tumor cells, a high apoptotic rate in primary breast cancer correlates with poor prognosis. The aim of this study was to investigate the incidence and the prognostic significance of apoptotic disseminated tumor cells (DTC) in the bone marrow (BM) of breast cancer patients who either underwent primary surgery or primary systemic chemotherapy (PST).Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 25 publications
(31 reference statements)
1
15
2
1
Order By: Relevance
“…However, there was no significant difference in serum levels of this marker based on hormone receptor or other tumor characteristics (9). The results of Tas et al, Demiray et al and this study are however inconsistent with the findings of a research by Krawczyk et al, where the incidence of M30 in breast tumor tissue was investigated by immunohistochemistry and the results showed higher incidence of this cytokeratin in hormone-positive and HER2-positive subtypes and cancers with lower grade tumors (23). The results of the present study showed no significant relationship between changes in M30, M65 and M30/M65 ratio during chemotherapy and survival parameters.…”
Section: Discussioncontrasting
confidence: 93%
“…However, there was no significant difference in serum levels of this marker based on hormone receptor or other tumor characteristics (9). The results of Tas et al, Demiray et al and this study are however inconsistent with the findings of a research by Krawczyk et al, where the incidence of M30 in breast tumor tissue was investigated by immunohistochemistry and the results showed higher incidence of this cytokeratin in hormone-positive and HER2-positive subtypes and cancers with lower grade tumors (23). The results of the present study showed no significant relationship between changes in M30, M65 and M30/M65 ratio during chemotherapy and survival parameters.…”
Section: Discussioncontrasting
confidence: 93%
“…Our study is the first assessing the prognostic value of markers of apoptosis in DTCs of PC patients. In contrast to studies in breast cancer, a further characterization of cytokeratine positive DTCs into apoptotic and non‐apoptotic cells did not add any additional prognostic information to conventional pancytokeratine staining .…”
Section: Discussioncontrasting
confidence: 77%
“…Regarding the optimized aCTC cut-off, >50% reduction (n = <50% reduction (n = 49) showed a median PFS of 6 (5-10) vs. 3 (3-5) months (p = 0.0085) and a OS of 24 (17-34) vs. 10 (7-16) months (p < 0.0001). Regarding the optimized iCTC+aCTC >66.7% reduction (n = 57) vs. <66.7% reduction (n = 51) showed a median PFS of 6 (5-10) vs. months (p = 0.0063) and a median OS of 24 [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] vs. 10 (7-15) months (p = 0.0025). The impact of the optimized cut-offs on OS and PFS is shown in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…In 52-79% of CTC-positive MBC patients, aCTCs have been observed in peripheral blood samples [17][18][19]. They are thought to be a product of therapy-induced and/or spontaneous apoptosis [20,21]. Whatever the cause of apoptosis may be, significantly higher aCTC counts were detected in patients with MBC than in those with early breast cancer [22].…”
Section: Introductionmentioning
confidence: 99%